Evaluasi Karakteristik Fisik dan Kimia Produk Bubuk Kakao di Indonesia - Dewi Amrih; Syarifah, Atika Nur; Sutakwa, Adi; L, Mariani (Pro Food, 2025)
Cocoa (Theobroma cacao L.) is a plant that produces the main raw material for the chocolate industry. Cocoa plants are spread throughout tropical countries in the world, such as Indonesia, South America, and Africa. Cocoa beans can be turned into a range of processed chocolate goods, such as chocolate bars and cocoa powder, to raise their economic value. The characteristics of cocoa in each region have different characteristics depending on the factors of the planting process in the region and the processing process. This study will compare the characteristics of cocoa powder from various regions in Indonesia such as Yogyakarta, Jember, Lampung, Aceh, Kendari, and Jayapura. Moisture content of cocoa powder ranges 4.23-11,86, ash content ranges 4,06-10,58, protein content ranges 16,10-24,99, fat content ranges 11,75-40,37, and carbohydrate content by difference ranges 34,83-48,24. The physical analysis in this study includes fineness analysis with a range of 99.27%-99.70 %, color test using the Hunter Method with L value ranging from 29.79 to 42.05, a* value ranging from 17.65 to 24.71, b* value ranging from 18.75 to 26.29, and pH analysis with a range of 5.74-6.93. In conclusion, there are differences in the characteristics of cocoa powder between regions in Indonesia. The differences in environmental factors and processing processes in each area make cocoa powder's nutritional content and physical properties different.